Guttmann's ingenuity : The Paralympic Games as legacy of the Second World War (Historia, 2021)
In February 1944, the British government requested that Jewish German neurologist Dr Ludwig Guttmann set up a National Spinal Injuries Unit at Stoke Mandeville Hospital near Aylesbury, England. The main task of the unit was to take care of the numerous soldiers and civilians suffering from spinal cord injuries (paraplegics and tetraplegics) because of the Second World War. Starting the unit from scratch, Guttmann introduced a revolutionary new programme of treatment and rehabilitation in which sport was incorporated as a form of remedial exercise and a means of social reintegration and recognition. The use of sport as part of the treatment was so successful that it led to the Stoke Mandeville Games in 1948. Four years later, the games became an international event when a team of paraplegic war veterans from the Netherlands crossed the sea to compete against their British counterparts. The International Stoke Mandeville Games continued on an annual basis and in 1960, they were held outside England for the first time. The International Stoke Mandeville Games of 1960 took place in Rome shortly after the completion of the Olympic Games and became commonly known as the Paralympics. The Paralympics grew in stature and by 2012, based on spectator numbers the event became the third largest sporting event in the world. To many fans, the Paralympic Games is an exciting, yet very emotional event to watch and enjoy. Very few of these fans actually realise that the Paralympics are a legacy of the brutality of the Second World War.  In Februarie 1944 het die Britse regering die Joods-gebore Duitse neurochirurg Dr Ludwig Guttmann gevra om die National Spinal Injuries Unit by Stoke Mandeville hospitaal naby Aylesbury in Engeland te bestuur. Die vernaamste taak van die eenheid was om na die talle soldate en burgerlikes wat rugmurgbeserings opgedoen het (parapleë en tetrapleë) as gevolg van die Tweede Wêreldoorlog om te sien. Guttmann het die eenheid van nuuts af opgebou en het 'n revolusionêre nuwe program van behandeling en rehabilitasie gebruik as 'n vorm van regstellende oefening en 'n middel van sosiale integrasie en erkenning vir sy pasiënte. Die gebruik van sport as deel van die behandeling was so suksesvol dat dit gelei het tot die ontstaan van die Stoke Mandeville Spele in 1948. Vier jaar later het die Spele internasionale status verwerf toe 'n span Nederlandse oorlogsveterane teen hul Britse eweknieë kom kompeteer het. Die Internasionale Stoke Mandeville Spele is daarna jaarliks aangebied. In 1960 is dit net na die Olimpiese Spele, ook in Rome, aangebied, en het bekend geword as die eerste Paralimpiese Spele. Die Paralimpiese Spele het toegeneem in statuur en na die 2012 Spele in Londen was dit gevestig as die derde grootste toeskouersport ter wêreld. Vir menigte sport entoesiaste is die Paralimpiese Spele opwindend, dog baie emosioneel om te volg. Baie min van hierdie entoesiaste besef egter dat die Paralimpiese Spele 'n direkte uitvloeisel is van die wreedhede van die Tweede Wêreldoorlog.
Keywords: Paralympic Games; Paralimpiese Spele; Sports history; Ludwig Guttmann; Sport history